Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s11240-005-6307-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of morphological parameters of Grand Nain banana (Musa AAA) after in vitro multiplication with growth retardants

Abstract: The incorporation of growth retardants (GR) such as ancymidol (ANC) or paclobutrazol (PBZ) in liquid culture media during multiplication stage of bananas decreases the excessive growth of stems and leaves. However, it is unknown if these chemicals have residual effect on further plant growth. To study the effect of ANC and PBZ on Grand Nain banana shoots, they were subcultured for five cycles in the multiplication stage and evaluated in elongation-rooting and acclimatization stages. Multiplication basal medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
1
5
0
4
Order By: Relevance
“…Moreover, the study also revealed that optimum usage of this growth retardant (1 mg L -1 ) slightly enhanced the shoot production along with considerable reduction of shoot growth to 50%. Similar findings were reported previously, where PBZ application reduced longitudinal growth of shoots in 'Grand Nain' (Albany et al, 2005), 'Williams' (Jiachuan et al, 1999). PBZ also supported enhanced bud production and here we report 17% increase in the rate of production.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the study also revealed that optimum usage of this growth retardant (1 mg L -1 ) slightly enhanced the shoot production along with considerable reduction of shoot growth to 50%. Similar findings were reported previously, where PBZ application reduced longitudinal growth of shoots in 'Grand Nain' (Albany et al, 2005), 'Williams' (Jiachuan et al, 1999). PBZ also supported enhanced bud production and here we report 17% increase in the rate of production.…”
supporting
confidence: 90%
“…Moreover, aseptic handling of overgrown culture is very difficult. A growth retardant has been used along with cytokinins to boost bud development and to reduce shoot growth in vitro (Albany et al, 2005;Daquinta et al, 2001). Enhancing the shoot production and reducing the culture growth are of great importance in mass multiplication of banana.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Al respecto se ha demostrado que las condiciones de los sistemas de inmersión temporal (SIT) y de los medios líquidos en agitación orbital favorecen un mayor crecimiento de tallos y hojas que no son aprovechables para la etapa de multiplicación (Albany et al, 2006(Albany et al, y 2005.…”
Section: Establecimiento In Vitro En Medio Líquido Y Gelificadounclassified
“…Tal anormalidade prejudica o desenvolvimento dos cachos e dos frutos. A difi culdade em detectar esta variação, antes do repasse destas para os agricultores, tem limitado a utilização da propagação em bananeiras (Sandoval et al, 1999;Albany et al, 2005).…”
Section: Introductionunclassified
“…Tal anormalidade prejudica o desenvolvimento dos cachos e dos frutos. A difi culdade em detectar esta variação, antes do repasse destas para os agricultores, tem limitado a utilização da propagação em bananeiras (Sandoval et al, 1999;Albany et al, 2005).As causas para as diversas variações somaclonais em bananeiras ainda parecem bastante incertas. Porém, sugerese que muitas dessas anomalias podem estar relacionadas a distúrbios no metabolismo das giberelinas.…”
unclassified